Sosialisasi dan Pendampingan Table Manner untuk Anak-Anak Difabel - Lukita, Chandra; Akbari, Safitri; Gitama, Gytha Nurhana Dhea Praadha; Magdalena, Lena; Kusnadi, Kusnadi; Parman, Suhadi; Suwandi, Suwandi (Penerbit Goodwood, 2024)
Purpose: This social activity aims to help children with disabilities build better selves by Improving Social Skills, Increasing Self-Confidence, Improving Quality of Life. Methodology: The method used in this community service activity is carried out in several stages: preparation, program planning, material development, activity implementation, evaluation and feedback, reporting, and documentation. Results: The results obtained from community service activities with the theme Table manner training for disabled children show that disabled children can experience improved social skills, such as the ability to communicate better, interact with other people, and understand the norms of social behavior. In addition, by gaining an understanding of eating etiquette and improving table manners skills, children with disabilities can feel more confident when dining at restaurants, formal meetings, and social events. Limitation: The limitation in this social activity is that the length of time for carrying out the table-manner activity is very limited, considering that this activity is carried out at a hotel in Cirebon City, and the time is limited according to the rental price of the place at the hotel. Contribution: Socialization activities and Table-manner assistance have an important contribution to efforts to build better selves for children with disabilities. Through Table manner assistance, children with disabilities can learn how to eat properly, arrange eating utensils, and behave politely while eating. This can increase their independence in daily life. Socialization activities and Table-manner assistance can also increase social awareness among UCIC Cirebon student lecturers. They can better understand the needs of children with disabilities and become advocates in the community.